In Situ Periodic Regeneration of Catalyst during CO2 Electroreduction to C2+ Products - Xu, Liang; Ma, Xiaodong; Wu, Limin; Tan, Xingxing; Song, Xinning; Zhu, Qinggong; Chen, Chunjun; Qian, Qingli; Liu, Zhimin; Sun, Xiaofu; Liu, Shoujie; Han, Buxing (Angewandte Chemie International Edition, 2022)
Developing electrocatalytic reactions with high‐efficiency can make important contributions to carbon neutrality. However, poor long‐term stability of catalysts is a bottleneck for its practical application. Herein, an “in situ periodic regeneration of catalyst (PR‐C)” strategy is proposed to give long‐term high efficiency of CO2 electroreduction to generate C2+ products over Cu catalyst by applying a positive potential pulse for a short time periodically in the halide‐containing electrolyte. The high Faradaic efficiency (81.2 %) and current density (22.6 mA cm−2) could be maintained completely at least 36 h, while the activity and selectivity decreased continuously without using the PR‐C method. Control experiments and operando characterization demonstrated that the surface structure and oxidation state of Cu could be recovered periodically by the PR‐C method, which was beneficial for CO2 activation and C−C coupling. An “in situ periodic regeneration of catalyst (PR‐C)” strategy is proposed to maintain the high efficiency of CO2 electroreduction towards C2+ products over a copper catalyst. A positive potential pulse is applied periodically for a short time in the halide‐containing electrolyte. As a result the surface structure and oxidation state of the Cu could be recovered periodically by the PR‐C method.